2018
DOI: 10.1556/650.2018.30885
|View full text |Cite
|
Sign up to set email alerts
|

Az albumin prognosztikai jelentősége az onkológiában

Abstract: A szérumalbuminszint csökkenése figyelhető meg gyulladásos folyamatokban. A helyileg előrehaladott vagy áttétes rosszindulatú daganatokban a szérumalbuminszint ugyancsak csökken, az alultápláltság fennállásától függetlenül. A csökkent albuminszint befolyásolhatja a terápia eredményeit is (például gyógyszerek farmakokinetikája, mellékha-tások mértéke). Kiterjedt szakirodalmi adat és gyakorlati tapasztalat bizonyítja a táplálásterápiában részesülő pácien-sek jobb prognózisát. A szerzők a fontosabb szakirodalmi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Based on our results, we can confirm that a combination of biomarkers probably has a better prognostic value than any of the single biomarkers (Table 5). Other prognostic threshold values published in previous studies were comparable to our results (16,19,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on our results, we can confirm that a combination of biomarkers probably has a better prognostic value than any of the single biomarkers (Table 5). Other prognostic threshold values published in previous studies were comparable to our results (16,19,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionsupporting
confidence: 92%
“…In a locally advanced and/or metastatic setting, serum albumin level diminishes independently in the presence of malnutrition. Lower baseline albumin suggests poor survival (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of albumin can reveal the nutritional status of cancer patients, and low albumin level stands for the malnutrition of cancer patients, which can result in the poor prognosis and increase the cancer-related mortality. [ 23 , 24 ] A previous study containing 604 patients with OC showed low albumin was associated with higher complication rate and worse OS after the cytoreductive surgery. [ 25 ] On the other hand, it has already been proved that inflammation is associated with the proliferation, migration, immune escape, and chemoresistance of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…CRP and albumin represent acute phase reactants, although the concentrations move in opposite directions (21). The correlation of these acute phase reactants with neopterin concentrations, and the correlations between acute phase reactants or neopterin and hemoglobin concentration or platelet count have been amply documented in patients with solid tumors, as well as in patients with different nonmalignant conditions associated with inflammation (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%